Effects of Capsaicin on Growth Performance, Meat Quality, Digestive Enzyme Activities, Intestinal Morphology, and Organ Indexes of Broilers - Li, Zhihua; Zhang, Jiaqi; Wang, Ting; Zhang, Jingfei; Zhang, Lili; Wang, Tian (Frontiers in Veterinary Science, 2022)
This experiment was conducted to investigate the effects of capsaicin (CAP) on growth performance, meat quality, digestive enzyme activities, intestinal morphology, and organ indexes of broilers. A total of 256 one-day-old Arbor Acre male broilers were randomly allocated into four treatments with eight replicates of eight birds, feeding a basal diet (control group), a basal diet supplemented with 2, 4, and 6 mg/kg CAP for 42 d, respectively. The growth performance, digestive enzyme activities of intestinal contents, small intestinal morphology, and organ indexes were measured at 21 and 42 d. The meat quality traits of breast muscles were determined at 42 d. The results showed dietary 4 mg/kg CAP supplementation decreased (P < 0.05) the feed to gain ratio (F/G) in the grower phase (22–42 d) and overall (1–42 d) compared with the control group, and 2 mg/kg CAP group also decreased (P < 0.05) the F/G from 1 to 42 d. Dietary 4 mg/kg CAP supplementation decreased (P < 0.05) the drip loss at 48 h and the pH24h of breast muscles relative to the control group. Some digestive enzymes activities of jejunal and ileal contents were increased in the 2 and 4 mg/kg CAP groups compared with the control group both at 21 and 42 d. In addition, dietary 2 mg/kg CAP supplementation increased (P < 0.05) the relative weight of liver, jejunal villus height, villus width, and villous surface area at 21 d; The length of the jejunum segment and the relative weight of Bursa of Fabricius at 42 d in the 4 mg/kg CAP group were higher (P < 0.05) than the control group. In conclusion, dietary 2 or 4 mg/kg CAP supplementation decreased the F/G, improved meat quality, enhanced digestive enzyme activities, improved the jejunal development, and increased the relative liver and Bursa of Fabricius weight in broilers.